Recurvosides A - E, new polyhydroxylated steroidal saponins from Nolina recurvata stems - Takaashi, Yoko; Mimaki, Yoshihiro; Kuroda, Minpei; Sashida, Yutaka; Nikaido, Tamotsu; Ohmoto, Taichi (Tetrahedron, 1995)
A series of five new polyhydroxylated steroidal saponins, named recurvosides A - E, were isolated from the stems of Nolina recurvata (Agavaceae). Their structures were determined through detailed interpretation of various spectra, including two-dimensional (2D) NMR, and by acid-catalized hydrolysis. Among them, recurvoside E was revealed to be very unique in structure being a trisdesmoside with a β- d-fructofuranose as the monosaccharide component attached to the C-21 hydroxyl group of the aglycone. The isolated saponins were evaluated for inhibitory activity on cAMP phosphodiesterase as a primary screening test to find new biologically active compounds. The structures of recurvosides A ( 1) – E ( 5) were determined by extensive 2D NMR analysis and hydrolysis.